Comparative Effect of Burst Transcutaneous Electrical Nerve Stimulation (Tens) Versus Interferential Therapy (Ift) Along With Exercise In Reducing Pain and Functional Impairtment in Subjects with Knee Osteoarthritis. - Mukharjee, Mahima; Prabhakar, Ronald (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Osteoarthritis is a condition characterized by progressive loss of articular cartilage within a joint resulting in a pain. Osteoarthritis is more commonly seen in weight bearing joints i.e. knee joint. Radiologically and pathologically changes of osteoarthritis are seen in age of above 65 years. Because the knee joint is weight bearing and contributes to ambulation, patients usually experience functional limitations in activities of daily living. Materials & Methodology: Patients with knee Osteoarthritis (n=20) were included in this study and patients with traumatic injury to knee, or any recent surgical intervention performed at knee and Neurological illness were excluded from the study. A comparative study was done where two groups were made, Group A (n=10) received burst transcutaneous electrical nerve stimulation along with exercises and Group B (n=10) received interferential therapy along with exercise .Treatment was given for 5 times a week for 2 weeks. Pain was assessed using Visual Analogue Scale and functional disability was assessed using Western Ontario and McMaster Universities Osteoarthritis Index. Results: Group B showed significant decrease in pain and functioning as compared to Group A. Mean pre VAS of Burst TENS subjects was 5.90 which was significantly higher than mean post VAS 4.00 (P=0.06) Mean pre VAS of IFT subjects was 6.50 which was significantly higher than mean post VAS 2.90 (p<0.001). Mean pre WOMAC of Burst TENS subjects was 64.90 which was significantly higher than mean post WOMAC 45.60 (p<0.01). Mean pre WOMAC of IFT subjects was 67.50 which was significantly higher than mean post WOMAC 20.70 (p<0.01). Conclusion: The study concluded that Interferential Therapy along with Exercises is more effective than Burst Transcutaneous Electrical Nerve Stimulation along with Exercise.